Pre-Service Teachers' Understanding And Awareness Of Sustainable Development Concepts And Traditional Environmental Concepts - Karpudewan, Mageswary; Ismail, Zurida; Mohamed, Norita (Penerbit Universiti Sains Malaysia, 2013)
This paper discusses the findings from a survey conducted to investigate the level of awareness and understanding of traditional environmental concepts and sustainable development concepts among pre-service teachers. The survey involved 110 pre-service teachers enrolled in the chemistry teaching methods course. The student teachers were requested to complete a set of 20-item questionnaire on environmental knowledge. Awareness and understanding of concepts central to sustainable development is particularly significant for the pre-service teachers who are required to educate and promote education for sustainable development. Results of the study showed that the preservice teachers have a low level of awareness and understanding of concepts central to sustainable development compare to traditional environmental concepts. Recognising the importance of sustainability knowledge in leading sustainable lifestyle, the findings of this paper emphasise the need impart sustainable development knowledge through teaching and learning process